2005
DOI: 10.1073/pnas.0501390102
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing breast cancer by using Raman spectroscopy

Abstract: We employ Raman spectroscopy to diagnose benign and malignant lesions in human breast tissue based on chemical composition. In this study, 130 Raman spectra are acquired from ex vivo samples of human breast tissue (normal, fibrocystic change, fibroadenoma, and infiltrating carcinoma) from 58 patients. Data are fit by using a linear combination model in which nine basis spectra represent the morphologic and chemical features of breast tissue. The resulting fit coefficients provide insight into the chemical͞morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
464
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(477 citation statements)
references
References 35 publications
10
464
0
3
Order By: Relevance
“…The apparent decrease in triolein as cancer progresses could be due to: (1) the reduction of subcutaneous fat sampled by the probe, caused by the thickening epidermis during lesion formation; and/or (2) the reduction of membrane lipid synthesis induced by UV damage [34]. Because subcutaneous fat exists in a substantial amount and has large Raman scattering cross section [41] we believe (1) is the major reason. The thickening of epidermis originates from the progression of malignancy [42].…”
Section: Discussionmentioning
confidence: 99%
“…The apparent decrease in triolein as cancer progresses could be due to: (1) the reduction of subcutaneous fat sampled by the probe, caused by the thickening epidermis during lesion formation; and/or (2) the reduction of membrane lipid synthesis induced by UV damage [34]. Because subcutaneous fat exists in a substantial amount and has large Raman scattering cross section [41] we believe (1) is the major reason. The thickening of epidermis originates from the progression of malignancy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were also reported in previous studies using other optical spectroscopy techniques for breast tissue characterization. 44 Haka et al 44 used Raman spectroscopy for the diagnosis of breast cancer, and found that there was increased contribution from collagen in benign and cancerous breast tissues, relative to that in normal breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectroscopy has been proposed as a non-invasive and label free analytical method with a very consistent and prolific track record of in-vitro biomedical applications [22][23][24] for histopathological screening [25][26][27][28][29] as well as probing of lymph node pathology using fibre probes [30][31][32].…”
Section: Introductionmentioning
confidence: 99%